Hubungan Antara Personal Hygiene dan Kejadian Infeksi Enterobiasis Pada Siswa Sekolah Dasar Negeri Mojorejo 01 Bendosari Sukoharjo - Rosdania, Erlieza (2016)
Background : Enterobiasis incidence around 200 million people in the world, the highest prevalence was found in children primary school age and become one of the common infection to children in developing countries such as Indonesia. One of the risk factor of the infection was poor personal hygiene. Objective : Determine and analyze the relationship between personal hygiene and incidence of enterobiasis on students in Elementary School Mojorejo 01 Bendosari Sukoharjo. Methods : The design of the research was analytic observational research by employing cross sectional approach. The amount sample were 45 respondents with purposive sampling. The data obtained by anal swab test, interview and questionnaire. The data were analyzed by using fisher test and SPSS program. Result : Based on result of statistical fisher test between personal hygiene and incidence of enterobiasis variables was obtained a significant probability value p (sig) 0,002. Conclusion : There was significant relationship between personal hygiene and incidence of enterobiasis on students in Elementary School Mojorejo 01 Bendosari Sukoharjo